Predicate Analysis with Block-Abstraction Memoization - Wonisch, Daniel; Wehrheim, Heike (Proceedings of the 14th International Conference on Formal Engineering Methods (ICFEM))
Predicate abstraction is an established technique for reducing the size of the state space during verification. In this paper, we extend predication abstraction with block-abstraction memoization (BAM), which exploits the fact that blocks are often executed several times in a program. The verification can thus benefit from caching the values of previous block analyses and reusing them upon next entry into a block. In addition to function bodies, BAM also performs well for nested loops. To further increase effectiveness, block memoization has been integrated with lazy abstraction adopting a lazy strategy for cache refinement. Together, this achieves significant performance increases: our tool (an implementation within the configurable program analysis framework CPAchecker) has won the Competition on Software Verification 2012 in the category “Overall”.

Optimale Zuteilung von Nutzern zu verteilten Cloud-Standorten - Rojahn, Tobias

Local strategies for robot formation problems - Kempkes, Barbara
Wir betrachten eine Gruppe von mobilen, autonomen Robotern in einem ebenen Gelände. Es gibt keine zentrale Steuerung und die Roboter müssen sich selbst koordinieren. Zentrale Herausforderung dabei ist, dass jeder Roboter nur seine unmittelbare Nachbarschaft sieht und auch nur mit Robotern in seiner unmittelbaren Nachbarschaft kommunizieren kann. Daraus ergeben sich viele algorithmische Fragestellungen. In dieser Arbeit wird untersucht, unter welchen Voraussetzungen die Roboter sich auf einem Punkt versammeln bzw. eine Linie zwischen zwei festen Stationen bilden können. Dafür werden mehrere Roboter-Strategien in verschiedenen Bewegungsmodellen vorgestellt. Diese Strategien werden auf ihre Effizienz hin untersucht. Es werden obere und untere Schranken für die benötigte Anzahl Runden und die Bewegungsdistanz gezeigt. In einigen Fällen wird außerdem die benötigte Bewegungsdistanz mit derjenigen Bewegungsdistanz verglichen, die eine optimale globale Strategie auf der gleichen Instanz benötigen würde. So werden kompetititve Faktoren hergeleitet.

Introducing feedback to preemptive routing and wavelength assignment algorithms for dynamic traffic scenarios - Wette, Philip; Karl, Holger
Preemptive Routing and Wavelength Assignment (RWA) algorithms preempt established lightpaths in case not enough resources are available to setup a new lightpath in a Wavelength Division Multiplexing (WDM) network. The selection of lightpaths to be preempted relies on internal decisions of the RWA algorithm. Thus, if dedicated properties of the network topology are required by the applications running on the network, these requirements have to be known by the RWA algorithm. Otherwise it might happen that by preempting a particular lightpath these requirements are violated. If, however, these requirements include parameters only known at the nodes running the application, the RWA algorithm cannot evaluate the requirements. For this reason a RWA algorithm is needed which involves its users in the preemption decisions. We present a family of preemptive RWA algorithms for WDM networks. These algorithms have two distinguishing features: a) they can handle dynamic trafﬁc by on-the-ﬂy reconﬁguration, and b) users can give feedback for reconﬁguration decisions and thus inﬂuence the preemption decision of the RWA algorithm, leading to networks which adapt directly to application needs. This is different from trafﬁc engineering where the network is (slowly) adapted to observed trafﬁc patterns. Our algorithms handle various WDM network conﬁgurations including networks consisting of heterogeneous WDM hardware. To this end, we are using the layered graph approach together with a newly developed graph model that is used to determine conﬂicting lightpaths.

Identitätsbasierte Signaturen - Ein Sicherheitsbeweis für Signaturen auf Grundlage von Gap-Diffie-Hellman-Gruppen mit Hilfe des Forking-Lemmas - Löken, Nils

Identitätsbasierte Kryptographie - Implementierung von Paarungen für Körper der Charakteristik 2 - Haarhoff, Thomas

Heuristic-Guided Abstraction Refinement for Concurrent Systems - Timm, Nils; Wehrheim, Heike; Czech, Mike (Proceedings of the 14th International Conference on Formal Engineering Methods (ICFEM))
Predicate abstraction is an established technique in software verification. It inherently includes an abstraction refinement loop successively adding predicates until the right level of abstraction is found. For concurrent systems, predicate abstraction can be combined with spotlight abstraction, further reducing the state space by abstracting away certain processes. Refinement then has to decide whether to add a new predicate or a new process. Selecting the right predicates and processes is a crucial task: The positive effect of abstraction may be compromised by unfavourable refinement decisions. Here we present a heuristic approach to abstraction refinement. The basis for a decision is a set of refinement candidates, derived by multiple counterexample-generation. Candidates are evaluated with respect to their influence on other components in the system. Experimental results show that our technique can significantly speed up verification as compared to a naive abstraction refinement.

Distributed Computing in Fault-Prone Dynamic Networks - Brandes, Philipp; Meyer auf der Heide, Friedhelm (Proceedings of the 4th Workshop on Theoretical Aspects of Dynamic Distributed Systems (TADDS))
Dynamics in networks is caused by a variety of reasons, like nodes moving in 2D (or 3D) in multihop cellphone networks, joins and leaves in peer-to-peer networks, evolution in social networks, and many others. In order to understand such kinds of dynamics, and to design distributed algorithms that behave well under dynamics, many ways to model dynamics are introduced and analyzed w.r.t. correctness and eciency of distributed algorithms. In [16], Kuhn, Lynch, and Oshman have introduced a very general, worst case type model of dynamics: The edge set of the network may change arbitrarily from step to step, the only restriction is that it is connected at all times and the set of nodes does not change. An extended model demands that a xed connected subnetwork is maintained over each time interval of length T (T-interval dynamics). They have presented, among others, algorithms for counting the number of nodes under such general models of dynamics.In this paper, we generalize their models and algorithms by adding random edge faults, i.e., we consider fault-prone dynamic networks: We assume that an edge currently existing may fail to transmit data with some probability p. We rst observe that strong counting, i.e., each node knows the correct count and stops, is not possible in a model with random edge faults. Our main two positive results are feasibility and runtime bounds for weak counting, i.e., stopping is no longer required (but still a correct count in each node), and for strong counting with an upper bound, i.e., an upper bound N on n is known to all nodes.

Coverage Criteria for Testing DMM Specifications - Arifulina, Svetlana; Engels, Gregor; Soltenborn, Christian (Proceedings of the 11th International Workshop on Graph Transformation and Visual Modeling Techniques (GT-VMT))
Behavioral modeling languages are most useful if their behavior is specified formally such that it can e.g. be analyzed and executed automatically. Obviously, the quality of such behavior specifications is crucial. The rule-based semantics specification technique Dynamic Meta Modeling (DMM) honors this by using the approach of Test-driven Semantics Specification (TDSS), which makes sure that the specification at hand at least describes the correct behavior for a suite of test models. However, in its current state TDSS does not provide any means to measure the quality of such a test suite. In this paper, we describe how we have applied the idea of test coverage to TDSS. Similar to common approaches of defining test coverage criteria, we describe a data structure called invocation graph containing possible orders of applications ofDMM rules. Then we define different coverage criteria based on that data structure, taking the rule applications caused by the test suite’s models into account. Our implementation of the described approach gives the language engineer using DMM a means to reason about the quality of the language’s test suite, and also provides hints on how to improve that quality by adding dedicated test models to the test suite.

Competitive and fair throughput for co-existing networks under adversarial interference - Richa, Andrea W.; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Proceedings of the 31st Annual ACM SIGACT-SIGOPS Symposium on Principles and Distributed Computing (PODC))
This paper initiates the formal study of a fundamental problem: How to efficiently allocate a shared communication medium among a set of K co-existing networks in the presence of arbitrary external interference? While most literature on medium access focuses on how to share a medium among nodes, these approaches are often either not directly applicable to co-existing networks as they would violate the independence requirement, or they yield a low throughput if applied to multiple networks. We present the randomized medium access (MAC) protocol COMAC which guarantees that a given communication channel is shared fairly among competing and independent networks, and that the available bandwidth is used efficiently. These performance guarantees hold in the presence of arbitrary external interference or even under adversarial jamming. Concretely, we show that the co-existing networks can use a Ω(ε2 min{ε, 1/poly(K)})-fraction of the non-jammed time steps for successful message transmissions, where ε is the (arbitrarily distributed) fraction of time which is not jammed.

Brief Announcement: SplayNets - Towards Self-Adjusting Distributed Data Structures - Schmid, Stefan; Avin, Chen; Scheideler, Christian; Häupler, Bernhard; Lotker, Zvi (Proceedings of the 26th International Symposium on Distributed Computing (DISC))
This paper initiates the study of self-adjusting distributed data structures for networks. In particular, we present SplayNets: a binary search tree based network that is self-adjusting to routing request.We derive entropy bounds on the amortized routing cost and show that our splaying algorithm has some interesting properties.

Multi-Modal, Multi-Touch Interaction with Maps in Disaster Management Applications - Paelke, Volker; Nebe, Karsten; Geiger, Christian; Klompmaker, Florian; Fischer, Holger Gerhard (ISPRS - International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)

Brief Announcement: Hashed Predecessor Patricia Trie - A Data Structure for Efficient Predecessor Queries in Peer-to-Peer Systems - Kniesburges, Sebastian; Scheideler, Christian (Proceedings of the 26th International Symposium on Distributed Computing (DISC))
The design of ecient search structures for peer-to-peer systems has attracted a lot of attention in recent years. In this announcement we address the problem of nding the predecessor in a key set and present an ecient data structure called hashed Predecessor Patricia trie. Our hashed Predecessor Patricia trie supports PredecessorSearch(x) and Insert(x) and Delete(x) in O(log log u) hash table accesses when u is the size of the universe of the keys. That is the costs only depend on u and not the size of the data structure. One feature of our approach is that it only uses the lookup interface of the hash table and therefore hash table accesses may be realized by any distributed hash table (DHT).

Block Abstraction Memoization for CPAchecker - Wonisch, Daniel (Proceedings of the 18th International Conference on Tools and Algorithms for the Construction and Analysis of Systems (TACAS))
Block Abstraction Memoization (ABM) is a technique in software model checking that exploits the modularity of programs during verification by caching. To this end, ABM records the results of block analyses and reuses them if possible when revisiting the same block again. In this paper we present an implementation of ABM into the predicate-analysis component of the software-verification framework CPAchecker. With our participation at the Competition on Software Verification we aim at providing evidence that ABM can not only substantially increase the efficiency of predicate analysis but also enables verification of a wider range of programs.

Basic Network Creation Games with Communication Interests - Cord-Landwehr, Andreas; Huellmann (married name: Eikel), Martina; Kling, Peter; Setzer, Alexander (Proceedings of the 5th International Symposium on Algorithmic Game Theory (SAGT))
Network creation games model the creation and usage costs of networks formed by a set of selfish peers.Each peer has the ability to change the network in a limited way, e.g., by creating or deleting incident links.In doing so, a peer can reduce its individual communication cost.Typically, these costs are modeled by the maximum or average distance in the network.We introduce a generalized version of the basic network creation game (BNCG).In the BNCG (by Alon et al., SPAA 2010), each peer may replace one of its incident links by a link to an arbitrary peer.This is done in a selfish way in order to minimize either the maximum or average distance to all other peers.That is, each peer works towards a network structure that allows himself to communicate efficiently with all other peers.However, participants of large networks are seldom interested in all peers.Rather, they want to communicate efficiently with a small subset only.Our model incorporates these (communication) interests explicitly.Given peers with interests and a communication network forming a tree, we prove several results on the structure and quality of equilibria in our model.We focus on the MAX-version, i.e., each node tries to minimize the maximum distance to nodes it is interested in, and give an upper bound of O(\sqrt(n)) for the private costs in an equilibrium of n peers.Moreover, we give an equilibrium for a circular interest graph where a node has private cost Omega(\sqrt(n)), showing that our bound is tight.This example can be extended such that we get a tight bound of Theta(\sqrt(n)) for the price of anarchy.For the case of general networks we show the price of anarchy to be Theta(n).Additionally, we prove an interesting connection between a maximum independent set in the interest graph and the private costs of the peers.

Designing Multi-Modal Map-Based Interfaces for Disaster Management - Paelke, Volker; Nebe, Karsten; Geiger, Christian; Klompmaker, Florian; Fischer, Holger Gerhard (Proceedings of the 5th International Conference on Advances in Computer-Human Interaction (ACHI))

Authenticated Tangible Interaction using RFID and Depth-Sensing Cameras - Supporting Collaboration on Interactive Tabletops - Klompmaker, Florian; Fischer, Holger Gerhard; Jung, Helge (Proceedings of the 5th International Conference on Advances in Computer-Human Interaction (ACHI))

Integrating usability engineering in the software development lifecycle based on international standards - Fischer, Holger Gerhard (Proceedings of the 4th ACM SIGCHI symposium on Engineering interactive computing systems - EICS '12)

Attribute-basierte Verschlüsselung - Schleiter, Patrick

Enriching Disaster Control Management based on Human-Computer Design - Fischer, Holger Gerhard; Klompmaker, Florian (Proceedings of the 9th International Conference on Information Systems for Crisis Response and Management (ISCRAM))